(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
The Impact of Work Environment and Motivation on Employee Performance at PT Perkebunan Nusantara II Kebun Tandem Hilir. The purpose of this study is to determine the influence of work environment and motivation on employee performance at the PT Perkebunan Nusantara II Kebun Tandem Hilir. The research population includes all 60 permanent employees of PT Perkebunan Nusantara II Kebun Tandem Hilir. The number of samples is determined using the Slovin formula with an error tolerance level of 10%. The samples include 38 people that are selected using purposive sampling method. The sample criteria in this study are all permanent employees and employees who have superiors who could assess the performance of these employees. Data were obtained through online interviews and documentation as well as a questionnaire where the variables are measured by giving a score of 1-5. The data is analyzed using the SEM-PLS analysis technique. The results show that work environment and motivation have a positive and significant effect on employee performance. The indicator that best reflects the work environment is quietness, while the weakest indicator is comfort. The indicator that best reflects work motivation is work it self, while the weakest indicator is achievement. Based on the original sample value in the study, it could be identified that the factor that influences employee performance is the work environment. The results of this study imply that the Manager of the PT Perkebunan Nusantara II Kebun Tandem Hilir must begin with efforts to increase motivation and the work environment.